2014
DOI: 10.1007/s00128-014-1350-2
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Bioaccumulation of Cyanobacterial Bioactive and Odorous Metabolites Occurred in a Large, Shallow Chinese Lake

Abstract: The distributions of cyanobacterial bioactive and odorous metabolites were investigated in the fifth largest lake in China in the fishing season 2012. The highest microcystins (MCs) concentration in water reached 3.4 lg L -1. A high b-ionone concentration reached 35.6 ng L -1 in water. Mean MCs concentration in muscle was highest in omnivorous Carassius auratus (20.9 ng g -1 dry weight), followed by phytoplanktivorous Hypophthalmichthys molitrix (7.4 ng g -1 DW) and carnivorous Coilia ectenes (3.0 ng g -1 DW).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The study concluded that the estimated daily intakes of MCs in 55.6% of the muscle samples exceeded the provisional TDI as high concentrations of MCs were detected in the analyzed muscle samples of these species (Table 3). Jiang et al detected lower concentrations of MCs using ELISA in both silver carp and crucian carp collected from Lake Chaohu than those previously reported in shrimps and mussels by other researchers [51,132,139]. However, the same authors detected much higher MCs concentrations using the same technique for detection (ELISA) in a different study [140].…”
Section: Occurrence Of Cyanotoxins In Seafood From the Developing Countries In Asiamentioning
confidence: 81%
“…The study concluded that the estimated daily intakes of MCs in 55.6% of the muscle samples exceeded the provisional TDI as high concentrations of MCs were detected in the analyzed muscle samples of these species (Table 3). Jiang et al detected lower concentrations of MCs using ELISA in both silver carp and crucian carp collected from Lake Chaohu than those previously reported in shrimps and mussels by other researchers [51,132,139]. However, the same authors detected much higher MCs concentrations using the same technique for detection (ELISA) in a different study [140].…”
Section: Occurrence Of Cyanotoxins In Seafood From the Developing Countries In Asiamentioning
confidence: 81%
“…Over the past years, algae-induced black blooms have occurred frequently in the west of Lake Taihu and caused serious disasters to ecological environment 16 . Although odor-producing cyanobacteria and odorous compounds have been frequently occurred in surface water of Lake Taihu 17 , odorants in sediment and their potential contribution to the overlying water have not been systematically investigated. We have studied the distributions of two odorous compounds in the overlying water and sediment of the typical sites of Taihu Lake 18 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a study conducted in a lake in China detected concentrations of 5.5 μg kg of β-cyclocitral À1 and 25.5 μg kg of β-ionone À1 in Coilia ectenes fish. 135 Recent studies have provided insights into the potential adverse effects of critical off-flavour compounds produced by cyanobacteria on zebrafish. These studies examined GEO, MIB, and β-ionone at environmentally relevant concentrations, revealing impacts on development, oxidative stress, apoptosis, and endocrine disruption in zebrafish embryo larvae.…”
Section: Carotenoidsmentioning
confidence: 99%